A comparison of government-owned companies in China and Singapore. - Lin, Danni. (2010)
In recent years, corporate governance systems employed by government-owned companies have received much attention. In particular, the effects of government ownership on these firms’ performance have been mixed. Government-owned companies from two vastly different Asian economies are used in this paper as comparisons. Specifically, key institutional features of SOEs from China – a control-based economy, and GLCs from Singapore – a market-oriented economy, are highlighted and compared in the first part of the paper. Subsequently, corporate governance is broken down into its individual internal and external mechanisms, followed by a discussion of the significance of each of these mechanisms in contributing to better firm performance in the Data Analysis section. The last part of the paper covers the impact of government ownership on the financial decisions of these government-owned companies, namely on the capital structure and dividend policies. Through regression, variables such as percentage of top shareholding which significantly affects the companies’ key financial decisions are identified as well.